Impacts of COVID-19 pandemic on hospitality and tourism students / Christy Bidder - Bidder, Christy (2022)
Tourism education is part of the complex tourism system as it provides professionally trained and qualified employees for the industry. Given the severe impacts of COVID-19 on tourism and the interconnected relationship between tourism education and the industry, the pandemic might have altered hospitality and tourism (HTM) students' perceptions toward the sector and, subsequently, their career intention. Against this backdrop, this study explores the pandemic's impacts on HTM students by analyzing the degree of change in their perceptions toward tourism and the effect of that potential perceptual change on their career intention before and after COVID-19. The study used a quantitative research design's retrospective pretest-posttest (RPP) model. Cluster sampling was used to draw the study sample, which comprised HTM students enrolled at several major HTM educational institutions in Malaysia. Descriptives were used to analyse the respondents' profile and program enrollment data, a t-test was used to examine the respondents' pre- and post-COVID-19 tourism perceptions, and correlation was used to explore the relationship between perception and career intentions. Key findings suggest that after COVID-19, HTM students have become less optimistic about the tourism industry and have lowered tourism-career intention after graduation. Additionally, such skills and knowledge as professional attitude and disciplinary skills might have become more critical and relevant. These findings underscore the importance of restoring HTM students' confidence and trust in tourism education and industry.